A Moral Hazard Approach to Wage Discounts under Informal Hiring. (6th March 2014) - Duran, Miguel A.; Morales, Antonio J.
Abstract This study discusses informal hiring in terms of a standard principal–agent model. We have developed an adverse selection model of the labour market where effort is not contractible and employers have the opportunity to use informal search channels for hiring purposes. This standard framework enables us to provide an effort‐based explanation of the wage gap associated with informal hiring. Besides the wage discount, another feature of the equilibrium is that low‐ability workers informally hired shirk.